Moisturizer Selection System According To Skin Type Using The Weighted Product Method - Sepriana Nurliani Harahap; M.Fakhriza (JURNAL TEKNOLOGI DAN OPEN SOURCE, 2025)
Choosing the right moisturizer for your skin type is an important aspect of skin care to maintain health and avoid problems such as irritation, dryness, or excess oil production. However, users often have difficulty finding the right choice due to the wide variety of products available on the market. Therefore, this study aims to develop a Decision Support System that can help users choose the most suitable moisturizer based on their skin type, by utilizing the Decision Tree method. This method is used because it is able to classify skin types based on various parameters, such as moisture level, sensitivity, oil content, and tendency towards acne. This system is built by processing a dataset containing skin characteristics and the appropriate moisturizer content. The results of the study show that the developed system has a high level of accuracy in providing recommendations according to needs. With this system, users can easily find the right moisturizer for their skin type, thus supporting more optimal skin care.